2007
DOI: 10.1021/ct700116n
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the Free and Bound Microstates of a Mobile Loop of α-Amylase Obtained from the Absolute Entropy and Free Energy

Abstract: Abstract:The hypothetical scanning molecular dynamics (HSMD) method is a relatively new technique for calculating the absolute entropy, S, and free energy, F, from a given sample generated by any simulation procedure. Thus, each sample conformation, i, is reconstructed by calculating transition probabilities that their product leads to the probability of i, hence to the entropy. HSMD is an exact method where all interactions are considered, and the only approximation is due to insufficient sampling. In previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(101 citation statements)
references
References 82 publications
(233 reference statements)
6
95
0
Order By: Relevance
“…26). The Jacobian is also omitted for simplicity because we have shown 13 that it cancels out (within the error bars) in entropy and free-energy differences (this conclusion was checked again and verified in the present study). The Boltzmann probability density corresponding to Z [Eq.…”
Section: Statistical Mechanics Of a Loop In Internal Coordinatessupporting
confidence: 78%
See 4 more Smart Citations
“…26). The Jacobian is also omitted for simplicity because we have shown 13 that it cancels out (within the error bars) in entropy and free-energy differences (this conclusion was checked again and verified in the present study). The Boltzmann probability density corresponding to Z [Eq.…”
Section: Statistical Mechanics Of a Loop In Internal Coordinatessupporting
confidence: 78%
“…In Ref. 13, we have shown that δα k and δα k+1 can be optimized. Notice that with HSMD the future loop conformations generated by MD at each step k' remain in general within the limits of m, which is represented by the analyzed MD sample.…”
Section: E the Hsmc(d) Methodsmentioning
confidence: 99%
See 3 more Smart Citations